Suspension Stability and Characterization of Chitosan Nanoparticle–Coated Ketoprofen Based on Surfactants Oleic Acid and Poloxamer 188 - Rasyid, Nur Qadri; Sugita, Purwantiningsih; Ambarsari, Laksmi; Syahbirin, Gustini (Makara Journal of Science, 2014)
In this research, ketoprofen was used as a drug model in the preparation of chitosan nanoparticles as a potential drug delivery system through the ionic gelation process with tripolyphosphate (TPP). The particle size analysis (PSA) revealed that the average particle size, polydispersity index (PI), and entrapment efficiency of chitosan nanoparticles prepared with oleic acid were 253.7 nm and 0.375 with drug entrapment efficiency of 73.30%. Those prepared with poloxamer 188 were 242.94 nm and 0.302 with drug entrapment efficiency of 87.89%. Scanning electron microscopy (SEM) analysis showed that the shapes of the nanoparticles, both prepared with oleic acid and poloxamer 188, were intact and spherical. Fourier transform infrared spectroscopy (FTIR) indicated several differences between the spectra of chitosan- and ketoprofen-loaded chitosan nanoparticles; for example, a new peak at the wavenumber 1409/cm indicated the presence of electrostatic interaction between the carboxyl group of ketoprofen and the amino group of chitosan. The chitosan nanoparticle suspension prepared with poloxamer 188 showed smaller increases in turbidity and viscosity than that prepared with oleic acid after 34 d of storage.